2018
DOI: 10.1002/anie.201808324
|View full text |Cite
|
Sign up to set email alerts
|

Transient Glass Formation around a Quadrupolar Photoexcited Dye in a Strongly H‐Bonding Liquid Observed by Transient 2D‐IR Spectroscopy

Abstract: Intermolecular H-bonding dynamics around aphotoexcited quadrupolar dye is directly observed using transient 2D-IR spectroscopy. Upon solvent-induced symmetry breaking, the H-bond accepting abilities of the two nitrile end-groups change drastically,a nd in extremely protic (superprotic) solvents,atight H-bond complex forms at one end. The time evolution of the 2D C Nlineshape in methanol points to rapid, 2-3 ps,spectral diffusion due to fluctuations of the H-bonding network. Similar behavior is observed in asup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 50 publications
0
21
0
2
Order By: Relevance
“…Whereas TRIR measurements proved to be the workhorse for monitoring ES-SB dynamics, [16][17][18][19]25,30,40,41 electronic transient absorption (TA) spectroscopy was less successful. However, we recently demonstrated that ES-SB can be visualised by monitoring the appearance of excited-state absorption (ESA) bands that are Laporte forbidden in the symmetric quadrupolar state.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas TRIR measurements proved to be the workhorse for monitoring ES-SB dynamics, [16][17][18][19]25,30,40,41 electronic transient absorption (TA) spectroscopy was less successful. However, we recently demonstrated that ES-SB can be visualised by monitoring the appearance of excited-state absorption (ESA) bands that are Laporte forbidden in the symmetric quadrupolar state.…”
Section: Resultsmentioning
confidence: 99%
“…Control on the extent of ES-SB can be achieved by tuning the properties of the local environment of the molecule with solvents of different polarity and H-bonding ability, [16][17][18][19][20]25,41 as well as the strength of D and A subunits. 30 The latter property is directly linked to the change of quadrupole moment upon excitation, which is also an important tuning parameter for ES-SB.…”
Section: Introductionmentioning
confidence: 99%
“…Это означает, что параметр малости в разложении по степеням параметра асимметрии (3) имеет порядок 0.01, что гарантирует высокую точность используемого приближения. Этот малый параметр позволяет также пренебречь влиянием квадратичного электронноколебательное взаимодействие U ИК полос, измеренных методами нестационарной 2D ИК спектроскопии [21]. Они приблизительно равны η s ∼ = η a = 10 cm −1 .…”
Section: дискуссияunclassified
“…Sedangkan klorin memiliki nomor atom 17, untuk stabil klorin menangkap 1 elektron dari atom lain. sehingga, jika natrium dengan klor berikatan, akan terjadi serah terima elektron yang menyebabkan mereka berikatan (49)(50)(51)(52) ionik. Ada dua atom penyusun NaCl yaitu natrium dan klor.…”
Section: Pendahuluanunclassified